2011
DOI: 10.1111/j.1755-3768.2011.02251.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure changes following 20G pars‐plana vitrectomy

Abstract: ABSTRACT.Purpose: To observe the excursions of short-term intraocular pressure (IOP) after 20-G pars-plana vitrectomy (ppV). Material and methods: In a prospective study, 851 patients (age: mean 63 ± 15 years) underwent unilateral ppV for various vitreoretinal diseases using different endotamponades [Balanced Salt Solution (BSS) 33.1%, Air 7.2%, SF 6 33.6%, silicon oil 5000 cst 26.1%]. Intraocular pressure was measured in all patients before and at 3, 6, 24 and 48 hr after surgery. Survival analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 23 publications
2
23
1
6
Order By: Relevance
“…In 2010, Höhn and Mirshahi11 assessed IOP after ranibizumab injection, in which mean IOP was 21.2 mm Hg before injection, 54.7, 43.4 and 28.3 mm Hg at 1, 3 and 10 min after injection, respectively. In 2011, Framme et al 12 reported IOP after 20-gauge pars-plana vitrectomy. The overall cumulative hazard to reach an IOP ≥ 30 mm Hg after 24 h was 23.9%, while IOP ≥ 40 mm Hg was 8.2%.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Höhn and Mirshahi11 assessed IOP after ranibizumab injection, in which mean IOP was 21.2 mm Hg before injection, 54.7, 43.4 and 28.3 mm Hg at 1, 3 and 10 min after injection, respectively. In 2011, Framme et al 12 reported IOP after 20-gauge pars-plana vitrectomy. The overall cumulative hazard to reach an IOP ≥ 30 mm Hg after 24 h was 23.9%, while IOP ≥ 40 mm Hg was 8.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Reports in the literature have suggested intra-ocular tamponade with gas, rather than fluid, does increase the risk of post-operative pressure spikes [25]. In particular, this spike is reported to occur at 24 hours post surgery following conventional 20-gauge vitrectomy [26]. Intra-ocular tamponade with C3F8 was more common in the 20-gauge compared to the 23-gauge group (68%, 34/50, compared to 44%, 22/50).…”
Section: Discussionmentioning
confidence: 99%
“…Framme et al [24] studied IOP after 20g surgery and found that transient low IOP was infrequent in 1.2% (10/851) of eyes. IOP after 25g surgery has been less frequently investigated.…”
Section: Discussionmentioning
confidence: 99%